THE SPIRITUAL INFLUENCE OF TEACHERS ON THE SPIRITUALITY OF STUDENTS - Muhasim Muhasim; Zulfikar Muhammad (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Humans as weak creatures must have strong principles in the life of this world. Students who do not have good motivation in learning, do not have enthusiasm for learning and are often frustrated with poor learning outcomes, this is due to students' lack of understanding of the meaning of life from a religious perspective. People with good spiritual intelligence will be good at responding to all things before, during, and after events. Teachers as educators have a role as good attitude or role models for their students. Therefore, this study wants to examine how the influence of the spiritual quotient of the teacher on the spiritual quotient of students. This research is a quantitative study using a crossectional approach. This study aims to determine how the influence of spiritual quotient on students' spiritual quotient. Collecting data using a questionnaire then analyzed. The research analysis using Wilcoxon with 95% significant values. This research was conducted at Senior High School of Muhammadiyah 1 Malang City in August 2020. The sample used was 75 respondents with a purposive sampling method of sampling. The results showed a very significant influence on the spiritual quotient of the teacher on the spiritual quotient of students with the number 0.003. So from the results of this study schools can apply spiritual education and apply it in their respective institutions Keywords Spiritual Quotient, Teachers, Students